Cu2O photocathodes for unassisted solar water-splitting devices enabled by noble-metal cocatalysts simultaneously as hydrogen evolution catalysts and protection layers. (23rd September 2019) - Wang, Yi-Chen; Qin, Chao; Lou, Zi-Rui; Lu, Yang-fan; Zhu, Li-Ping
Abstract: Here, we report a Cu2 O-based photocathode applied with pulsed-laser-deposited overlayers with the structure of Ga2 O3 /AZO/TiO2 and 60 nm dense Pt simultaneously as a hydrogen evolution catalyst and protective layer under backside illumination from ITO substrate. And by depositing thin Au nanoparticles on the bottom of Cu2 O, we observe the increase of light harvesting and the production of hot electrons from the surface plasmon resonance effect. The modified photocathode presents a photocurrent density of −4 mA cm −2 at 0 V versus reversible hydrogen electrode and a thermodynamically-based energy conversion efficiency of 0.27% in a weak acidic electrolyte. The stability is tremendously improved compared with other structures without the dense Pt layer. This enhancement is attributed to the formation of a p–n junction at the Cu2 O and Ga2 O3 interface and surface stabilization by TiO2 and Pt. To demonstrate the impact on the practical application of the photocathode, we fabricate the bias-free solar water-splitting tandem device using a transparent BiVO4 photoanode, which exhibits a stabilized peak photocurrent density of 0.1 mA cm −2 under continuous illumination.